TMIC-61. LOSARTAN PREVENTS IMMUNOTHERAPY-ASSOCIATED EDEMA AND ENHANCES SURVIVAL IN GLIOBLASTOMA. (14th November 2022) - Datta, Meenal; Chatterjee, Sampurna; Perez, Elizabeth; Gritsch, Simon; Roberge, Sylvie; Duquette, Mark; Chen, Ivy; Naxerova, Kamila; Kumar, Ashwin; Ghosh, Mitrajit; Emblem, Kyrre; Ng, Rosa; et al.
Abstract: Immune checkpoint blockers (ICBs) have revolutionized the treatment of some solid cancers but have failed to benefit the majority of glioblastoma (GBM) patients. Two reasons underlying limited ICB benefit are: 1) immune-related adverse events, and 2) resistance conferred by the tumor microenvironment. Here, we show that ICBs induce cerebral edema in patients and GBM mouse models. This edema results from an inflammatory response to ICB treatment that disrupts the blood-tumor-barrier, as confirmed by intravital imaging, mechanistic blocking studies, and single-cell RNA sequencing. Losartan – a commonly prescribed antihypertensive agent – controls ICB-induced edema, reprograms the immunosuppressive tumor microenvironment, and improves survival under ICB therapy. In combination with a standard of care regimen in mice mimicking clinical treatment (surgical resection, chemoradiation), losartan increases the percent of long-term surviving (cured) mice under ICB therapy from 16% to 43%. Finally, a bihemispheric "resect-and-response" model to establish predictive biomarkers from the tumor microenvironment reveals that cured mice have an immunostimulatory ("hot") immune tumor compartment prior to therapy. These results provide the basis for clinical testing of adding to losartan to ICB treatment for GBM patients.